2011
DOI: 10.1002/cne.22636
|View full text |Cite
|
Sign up to set email alerts
|

Neural cell adhesion molecule ablation in mice causes hippocampal dysplasia and loss of septal cholinergic neurons

Abstract: The neural cell adhesion molecule (NCAM) is implicated in nervous system development and plasticity. In humans, abnormal NCAM expression has been linked to the pathogenesis of neuropsychiatric and neurodegenerative disorders accompanied by cognitive dysfunctions. Impaired cognition is also observed in NCAM-deficient (NCAM(-/-) ) mice. Considering the importance of the septal cholinergic nuclei and the hippocampus for cognition, we performed quantitative morphological analyses of these areas in young and adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 100 publications
0
11
0
Order By: Relevance
“…Furthermore, a progressive decline in PSA-NCAM with age is observed in schizophrenia (Barbeau et al, 1995;Seki and Arai, 1999;Cox et al, 2009) and accompanies structural changes in the brain. Similarly to schizophrenic and elderly patients (Convit et al, 2001), brain size and weight are decreased in NCAM ÏȘ/ÏȘ mice (Wood et al, 1998;Tereshchenko et al, 2011). Overall, DCS ameliorates impairments related to schizophrenia (Javitt, 2006), other age-related brain pathologies (Mohr et al, 1995;Tsai et al, 1999), and deficits found in adult and aged NCAM ÏȘ/ÏȘ mice.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, a progressive decline in PSA-NCAM with age is observed in schizophrenia (Barbeau et al, 1995;Seki and Arai, 1999;Cox et al, 2009) and accompanies structural changes in the brain. Similarly to schizophrenic and elderly patients (Convit et al, 2001), brain size and weight are decreased in NCAM ÏȘ/ÏȘ mice (Wood et al, 1998;Tereshchenko et al, 2011). Overall, DCS ameliorates impairments related to schizophrenia (Javitt, 2006), other age-related brain pathologies (Mohr et al, 1995;Tsai et al, 1999), and deficits found in adult and aged NCAM ÏȘ/ÏȘ mice.…”
Section: Discussionmentioning
confidence: 93%
“…Whereas constitutive NCAM knockout mice have been much characterized (Theodosis et al 2004;Tereshchenko et al 2011;Kochlamazashvili et al 2012), information regarding the (neuro)-physiological impact of the mutation in NCAMffcre mice is scarce. However, available information indicates an existing vulnerability in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…We could exclude glial cells from these counts as their nuclei were easily recognizable by their small size compared with neuronal nuclei, but we were unable to distinguish nuclei of principal cells from interneurons, a fact that appears negligible in the context of our study, since interneurons, both PV‐positive and negative, are very rare (< 1%) in the principal cell layers compared with the overwhelming numbers of densely packed pyramidal or granule cells (Tereshchenko et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The cingulate cortical area Cg1‐Cg2 (Franklin and Paxinos ) and the subdivisions of the hippocampus (Tereshchenko et al . ) were identified and delineated on the basis of the nuclear staining pattern seen at low‐power magnification (10× objective). The border between the dorsal and ventral hippocampus in the coronal plane was defined to be at bregma −2.3 mm (Franklin and Paxinos ).…”
Section: Methodsmentioning
confidence: 99%